2015
DOI: 10.1002/jms.3605
|View full text |Cite
|
Sign up to set email alerts
|

Fast quantitative determination of methylphenidate levels in rat plasma and brain ex vivo by MALDI‐MS/MS

Abstract: This study presents a simple and sensitive high-throughput matrix-assisted laser desorption/ionization time-of-flight tandem mass spectrometry (MALDI-MS/MS) method for ex vivo quantification of methylphenidate (MPH) in rat plasma and brain. The common MALDI matrix alpha-cyano-4-hydroxycinnamic acid was used to obtain an optimal dried droplet preparation. For method validation, standards diluted in plasma and brain homogenate prepared from untreated (control) rats were used. MPH was quantified within a concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…[33] Besides, hardware advances regarding the sensitivity, laser frequency and MS/MS capabilities brought many advantages such as high detection sensitivity, resolution accuracy, low sample consumption and rapid detection, which all significantly improve LMW compound analytics. [16,17,[34][35][36] Utilizing the matrix suppression effect (MSE) can provide high quality MALDI mass spectra (strong analyte signals with weak or none background interferences) and was first introduced by McCombie and Knochenmuss. [37] The authors demonstrated that MSE can be achieved by adjusting factors such as laser intensity and the molar ratio between matrix and analyte in the sample.…”
Section: Strategies Allowing To Use Classic Matrices For Lmw Analytesmentioning
confidence: 99%
See 2 more Smart Citations
“…[33] Besides, hardware advances regarding the sensitivity, laser frequency and MS/MS capabilities brought many advantages such as high detection sensitivity, resolution accuracy, low sample consumption and rapid detection, which all significantly improve LMW compound analytics. [16,17,[34][35][36] Utilizing the matrix suppression effect (MSE) can provide high quality MALDI mass spectra (strong analyte signals with weak or none background interferences) and was first introduced by McCombie and Knochenmuss. [37] The authors demonstrated that MSE can be achieved by adjusting factors such as laser intensity and the molar ratio between matrix and analyte in the sample.…”
Section: Strategies Allowing To Use Classic Matrices For Lmw Analytesmentioning
confidence: 99%
“…For example, polyethyleneoxide (PEO)‐type surfactants, which can suppress the ionization of analytes due to their high ionization efficiency, can be removed by carefully washing with a methanol solution [33] . Besides, hardware advances regarding the sensitivity, laser frequency and MS/MS capabilities brought many advantages such as high detection sensitivity, resolution accuracy, low sample consumption and rapid detection, which all significantly improve LMW compound analytics [16,17,34–36] …”
Section: Utilizing Classic Matrices For Lmw Compound Analyticsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported a matrix-assisted laser desorption/ionization mass spectrometry (MALDI MS) absolute quantification method and demonstrated it for the estimation of ADMA and SDMA concentrations from urine 31 . For this study, an optimized and validated MALDI MS/MS method 32 has been employed to selectively measure ASR using the signature product ion ratio of ADMA and SDMA. The method was thoroughly tested for precision, accuracy, performance, and cross-platform validation (please see Supplemental Fig.…”
mentioning
confidence: 99%